2012
DOI: 10.1002/ijc.27729
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood infection of Kaposi's sarcoma‐associated herpesvirus in Zambian households: A molecular analysis

Abstract: Sub-Saharan Africa is endemic for Kaposi’s sarcoma-associated herpesvirus (KSHV) and there is a high rate of early childhood infection; however, the transmission sources are not well characterized. We examined household members as potential KSHV transmission sources to young children in the KSHV-endemic country of Zambia. To this end, we enrolled and followed Zambian households with at least one KSHV-seropositive child and collected longitudinal buccal swab samples. KSHV burden was evaluated and K1 sequences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…This suggests person-to-person contact with HHV-8 positive members is likely to play a key role in transmission. These results have been further confirmed by a study completed in our lab utilizing molecular analysis of the K1 gene sequence data of KSHV-positive individuals from nine households in our cohort (28). Olp et al found that in six of the nine households, the child had 100% sequence identify to all household members, supporting that intra-household transmission occurs (28).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This suggests person-to-person contact with HHV-8 positive members is likely to play a key role in transmission. These results have been further confirmed by a study completed in our lab utilizing molecular analysis of the K1 gene sequence data of KSHV-positive individuals from nine households in our cohort (28). Olp et al found that in six of the nine households, the child had 100% sequence identify to all household members, supporting that intra-household transmission occurs (28).…”
Section: Discussionsupporting
confidence: 80%
“…This finding has implications for public health risk, and the need for education of families of potential transmission of the virus when sharing food with young children, and needed behavior changes. Although the current analysis supports the view that the primary caregiver poses the most significant risk of transmitting HHV-8 infection to a child, other results from the same cohort also demonstrate that HHV-8 transmission to a child can also occur from other household members and even from others outside of the household (28). Whether similar factors are also associated with HHV-8 incident infection in “at-risk” children is the current focus of this study.…”
Section: Discussionsupporting
confidence: 45%
“…6). All K1 sequences clustered with genotypes A5 (n ϭ 1) or B (n ϭ 15), consistent with previous K1 genotyping of samples from Zambia (17). Within the B genotype, nine samples clustered with the subgenotype B1, two with B3, and four with B4.…”
Section: Figsupporting
confidence: 87%
“…The number of KSHV genomes in each KS biopsy sample was quantified before enrichment using the Bio-Rad QX100 droplet digital PCR (ddPCR) system. Human ␤-globin and KSHV ORF26 were amplified using primers and probes described previously (17). Each 20 l of ddPCR reaction mixture contained 1ϫ ddPCR Supermix (Bio-Rad), 900 nM concentrations of forward and reverse primer, 250 nM TaqMan probe, and 6 or 60 ng of genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…These data support the hypothesis that the transmission dynamics of HHV‐8 via saliva is established in populations in which there is a high seroprevalence of infected women of reproductive age. The amount and frequency of HHV appearing in saliva are likely determinants of risk for transmission . The high prevalence of HHV‐8 among Amerindians in Brazil, French Guiana, and the Equator, all considered hyperendemic areas for HHV‐8, supports the hypothesis of horizontal viral transmission via saliva .…”
Section: Discussionmentioning
confidence: 85%